An instrument to measure atrial fibrillation knowledge in Chinese patients: validation of the Jessa Atrial fibrillation Knowledge Questionnaire - Chang, Sijie; Xu, Wenlin; Wu, Shuyi; Desteghe, Lien; Zhang, Feilong; Zhang, Jinhua (Frontiers in Pharmacology, 2023)
Background: There is no validated tool to assess patients' knowledge of oral anticoagulant therapy in atrial fibrillation in China. Methods: Using a standard translation program, the Jessa Atrial fibrillation Knowledge Questionnaire（JAKQ）was translated into Chinese. The reliability of the JAKQ was assessed by internal consistency (Cronbach's α coefficient), repeatability (test-retest reliability), and sensitivity tests. Effectiveness was assessed by hypothesizing that a lower JAKQ score was a risk factor for bleeding. A total of 447 patients with atrial fibrillation (AF) who were hospitalized between July 2019 and December 2021 were studied and followed up. Participants were followed up 1, 3, 6, and 12 months after enrollment. Bleeding during follow-up was recorded. Data were obtained from hospital databases and telephone follow-up. Result: A total of 447 patients with AF completed JAKQ. The mean age of patients was 67.7±10.2 years. The median JAKQ score was 31.3% (12.5-43.8). The Cronbach's α coefficient of JAKQ was 0.616-0.637, and the test-retest reliability value was 0.902 (P<0.001). Multivariate logistic regression showed that the higher knowledge level of AF was associated with secondary education or above, an income of more than 2000 yuan, and a history of AF of more than 1 year. Bleeding was associated with a lower JAKQ score, hypertension, and a history of bleeding. Non-bleeding patients on VKA had a better understanding of how often INR should be monitored and what to do if an OAC dose was missed. Conclusion: The Chinese version of JAKQ shows good reliability and validity, indicating that it is a valuable tool for AF and oral anticoagulation (OAC) knowledge assessment. It can be used in clinical practice to guide educational activities and improve the effectiveness and safety of treatment. It was shown that Chinese patients with AF have insufficient knowledge about AF and OAC. Lower JAKQ scores are associated with bleeding, so targeted education is necessary. Targeted educational efforts should focus on patients recently diagnosed with AF and those with lower formal education and income.